(untitled) (Experimental biology, 2015)
The article describes the use against pests integrated and chemical methods. Pesticides, relating to the chemical method of protection , are physiologically active substances , depending on the regulations of their application , have a stimulatory or inhibitory effect on the physiological and biochemical processes in plants. Integrated protection aimed at preserving the biology and ecology of apple orchards , a safe environment , improve the quality of the final product obtained . Studied pesticides and plant growth regulator akpinol alpha affect biochemical indicator in apple fruits. Thus, the regulator of growth of plants the akpinol-alpha in the integrated option raises the content of sugar.